Rethinking Communication and Interaction. Challenges and Opportunities in Times of Crisis. Book of Abstracts - IANCU, Ioana; CULIC, Lorina; PAVELEA, Anișoara (Presa Universitară Clujeană, 2022)
Being already a tradition, the International Student’s Conference on Communication, organized by the Department of Communication, Public Relations and Advertising, Faculty of Political, Administrative and Communication Sciences, Babeș-Bolyai University, Cluj-Napoca, is celebrating its ninth edition (19 May 2021). The conference is developed in collaboration with the Communication and Social Innovation Research Center (CORE). Each year, the conference offers the bachelor, master and doctoral students the opportunity to share their research interests and their fascinating empirical results, to exchange ideas and feedback on their work, and to develop critical skills of analysis and presentation. Considering the pandemic context, the topic of the conference is Rethinking Communication and Interaction. Challenges and Opportunities in Times of Crisis. The present volume is a book of extended abstracts, enjoying the participation of 46 topics. The volume has six major chapters, out of which one is dedicated to the doctoral students.